Possible Fengyun-1C debris fall. Issue 10 (15th May 2017) - Golebiewska, J.; Nowak, M.; Muszyński, A.; Wnuk, E.
Highlights: A fall of small objects took place in Wargowo (Poland). After microscopic observations and chemical analysis a meteoritic origin of these objects was excluded. Analysis of orbital change and re-entry indicated space debris: 35127 Fengyun 1C as a possible source of the fall. Abstract: A fall of small objects took place on 27th April 2012 in Wargowo village near Oborniki, about 25 km NW from Poznań (Poland). There was only one eye-witness of the fall, who found two separate pieces (ca. 2.7 cm and ca. 2 cm), with several small additional fragments. After microscopic observations and chemical analysis a meteoritic origin of these objects was excluded. They are identified as space debris, therefore man-made. The most probable source of the observed fall was space debris 35127 Fengyun 1C DEB, created during destruction of the Chinese weather satellite Fengyun-1C (FY-1C).